The PUTRA press-fit system as an alternative femoral fixation technique for posterior cruciate ligament reconstruction – a technical note and outcome evaluation - Mohd Nasir, Mohd Nizlan; Hussin, Paisal; Yeak, Raymond Dieu Kiat; Saleh, Mohd Zaidi; Ahmad, Shahrulazua (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
We describe our technique of single-bundle PCL reconstruction using a bony femoral press-fit system. 9 patients underwent PCL reconstruction using our pressfit system. The surgical procedure is described in detail. Post-operatively, 5 patients were available for assessment and review. Four patients gave a final Lysholm score of 92 – 100%. Three patients gave a Hospital for Special Surgery (HSS) score of excellent, one fair and one poor. Two patients gave a reduced Tegner activity score post-operatively while the other three gave a similar score post-operatively. Assessment using KT-1000 revealed four patients with a side-to-side difference of less than 3 mm (average side-to-side difference, 1.87 mm), while one patient exhibited a side-to-side difference of 5.8 mm. We believe that our technique enhances tunnel healing through usage of a bone-plug fixation and provides a cheap alternative for graft fixation on the femoral side in PCL reconstruction.